The Utility of Collective Security in the Context of Human Security: The Yugoslav and Somali Experiences - Ebaye, Sunday Esoso Nsed; Bassey, Aimimi Paul (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2020)
When one examines closely the record of performance/non-performance of the UNSC at the crucial moments of the postCold War era, where major issues of peace and security are involved, including cases of human security crises, one finds that there is almost always tragic dilatoriness and/or lamentable inactions. While the UN was formed to ‘save succeeding generations from the scourge of war’ the list of scourges is growing. The real threats to international peace and security are no longer confined to violations of state sovereignty. Rather, new assertions of nationalism and sovereignty havesprung up, and the cohesion of States has been threatened by interstate conflict, poverty, infectious disease and environmental degradation, internal violence; including civil wars, genocide, ethnic-cleansing and state-failures, weapons-of-mass-destruction; including chemical, biological, radiological and nuclear-weapons, terrorism, and transnational-organized-crime, discrimination, and massive violations of human rights. All representing international security threats beyond the scope of any one state to solve. While the concept of peace may be easy to grasp, that of international security is more complex, for a pattern of contradictions has arisen. What is more worrisome is that each ofthese challenges is in a complex relationship of inter-linkage with each other. This paper intends to look at the changing scope of security, in the new environment of growing inter-linkage between peace-security-and-development, and to take a critical look at the new concept of human security and its implications to the treatment of the issue of collective-security in the UN. Data collection was through content analysis and analysed using the quantitative chi-square scientific method.Findings revealed that there is no significant relationship between collective-security in the context of human security and the resolution of the Yugoslav and Somali crises. The nature of today’s threats is such that no state, no matter how powerful, can unilaterally defend itself against these threats. These threats require global cooperation if they must be prevented. A situation where the UN appeared to be working together with a military-block to attain strategic objective  cannot guarantee international peace and security. The UN support for NATO occupation of former Yugoslavia is a negation of the UN-charter, and that the involvement of the U.S forces in the bombing of Somali, did not help the imageof the UN as the UN consciously or unconsciously allowed itself to be manipulated by a world power, seeking universal hegemony. The paper recommends: Aggressive economic development- that must advance the causes of securitydevelopment-and-human-rights together. Debt relief- as debts prevent the debt ridded countries from investing in productivity, thereby breeding unemployment and thus provide a ready market for conflict perpetrators. Reform of the economic-and-social-council- since the issues of peace-security-and-development are so inseparably interlinked, the powers and functions of the UNSC should include those socioeconomic issues of refugees, displaced persons, health- suchas HIV/AIDS, coronavirus, human rights violations, etc, threatening the basis of human-security. The paper concludes that the concept of security must undergo a major transformation from the traditional concept relating to protection against external threats to a State, to a much wider concept relating to the protection of human individuals against threats to their security as individuals.